The Role of Public Sphere According to Jurgen Habermas’s Perspective for Multicultural Societies in the Indonesian Context - Engki Prasutomo; Hengki Wijaya; Ivan Th. J. Weismann (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2019)
This paper explains the role of the public sphere based on Jurgen Habermas’s concept and analyzes its relevance for multicultural societies in the Indonesian Context. The public sphere exists to present democracy, tolerance, friendship, inclusivism in diversity, unity in diversity, and education. Indonesia is a country that reflects multiculturalism, can realize peace and unity within a multicultural frame. This article was developed using the Systematic Literature Review (SLR) method. This paper explains the role of public space based on Jurgen Habermas for interdisciplinary scholarship and its relevance. His findings show Jurgen Habermas's approach through the public sphere can bring about unity and peace in all aspects of life, including differences in beliefs and multicultural contexts.